The Effect Of Yoga Respiration (Pranayama) on Stress Reduction in The Elderly - Dwi Kusumadewi; Ramelan Sugijana; Wien Soelistya Adi (JENDELA NURSING JOURNAL, 2019)
Background : Aging is the process of slowly disappearing the ability of the network to improve itself. One of the mental health problems has by the elderly is stress. If stress is not overcome, it can affect the body's system. One of the ways to deal with stress is yoga respiration (pranayama).Purpose: The purpose of this study is to determine the effect of yoga respiration (pranayama) on stress reduction in the elderly at Wening Wardoyo Ungaran's Elderly Social Services Home.Methods: This study used quasy experimental design with one group pretestpost test study design. The sampling technique used was non probability sampling techniques as many as 30 respondents, sample selection used was the DASS 42 questionnaire. The analysis of the data used was the dependent t test / one sample test.Results: Based on the results of the dependent t test / one sample obtained p value = 0,000, it can be concluded that there is an effect of yoga respiration (pranayama) on stress reduction in the elderly at the  Wening Wardoyo Ungaran's Elderly Social Services Home.Conclusion: Yoga respiration (pranayama) to reduce stress for the elderly and can reduce the stress category of the elderly and score on the 42 DASS questionnaire.